EVALUASI KEBIJAKAN PENGEMBANGAN RUANG TERBUKA HIJAU DI KOTA MATARAM - sanapiah, ariy; sanapiah, airy (Magister Administrasi Publik FISIP Universitas Mulawarman, 2023)
Green open space (RTH) is an indicator of the livability of people in an area. RTH is very important because it has many benefits. Therefore, local governments have the responsibility to provide sufficient green open space in their administrative areas. Mataram City, as one of the regions in NTB Province, has problems related to green open spaces. The percentage of green open space in Mataram City is still below national standards and regional targets. Based on these problems, researchers are interested in conducting research with the aim of finding out the extent of the commitment and seriousness of the Mataram City Government in paying attention to green open spaces. This type of research is descriptive with a qualitative approach. Data collection was carried out by means of in-depth interviews, observation and documentation. Data analysis using interactive models. The research results show that the percentage of green open space in Mataram City of 7% is still below the target set by the government and also below the national target of 20%. This is work that the Mataram City government continues to do to pursue this target, so that the level of feasibility and public service to the community can be even better.